Optical Gain Characteristics of BGaAs/GaP Quantum Wells - Herbert S. Maczko; Robert Kudrawiec; Marta Gladysiewicz (IEEE Photonics Journal)
Light emitters integrated with Si platform are highly desirable for photonic integrated circuits, however, manufacturing them remains difficult. In this work, BGaAs/GaP quantum well (QW) structures are proposed as a promising solution of the challenge. These QWs can be grown on GaP/Si templates, which are intensively developed for recent years. An 8-band k·p model, envelope function approximation, self-consistency in solving of Schrödinger and Poisson equations with parabolic approximations of the indirect valleys and Fermi golden rule are used to calculate and analyze the material optical gain spectra of the QWs. A positive material gain is found for the QWs with 10–35% BAs mole fraction, with zinc-blende BGaAs epilayers grown on the GaP(001) substrates as direct gap semiconductors. It is predicted that such structures emit red light with wavelengths from the range of 730–690 nm. Optimal QWs widths for maximal TE and TM gain polarizations are below the critical thickness of BGaAs grown on the GaP(001). Presented results clearly indicate that BGaAs/GaP QW system is a very promising gain medium for Si-compatible photonic integrated circuits.